A Novel Magnetic Carbon Nanotubes Functionalized with Pyridine Groups: Synthesis, Characterization and Their Application as an Efficient Carrier for Plasmid DNA and Aptamer. Issue 24 (25th June 2018) - Kaboudin, Babak; Saghatchi, Fatemeh; Kazemi, Foad; Akbari‐Birgani, Shiva
Abstract: Magnetic functionalized multi‐walled carbon nanotubes have been synthesized, characterized and studied for therapeutically active nucleic acids interaction and delivery. In this study, pyridine functionalized magnetically was investigated for plasmid DNA and aptamer delivery. A thorough structural characterization of new carrierhas been carried out by means of transmission electron microscopy, scanning electron microscopy images, carbon, hydrogen and nitrogen elemental analysis, thermogravimetric analysis, vibrating‐sample magnetometer and spectroscopy. The magnetic properties of magnetic functionalized multi‐walled carbon nanotubes allow the directional control of conjugated nucleic acids with a transporter using an external magnetic field. They can be used as a transporter to afford noncovalent binding with nucleic acids and are supposed to cross the plasma membrane and internalize into the cytoplasm without inducing cell death. Abstract : Magnetic functionalized carbon nanotube as a carrier for plasmid DNA and aptamer: A novel magnetic functionalized carbon nanotube with a high capacity of carrying plasmid DNA and aptamer, very low cytotoxicity and fast transfer to the cell. Besides, they have the capability to be guided and recycled using a magnetic field.